Rhizobial exopolysaccharides: genetic control and symbiotic functions - Skorupska, Anna (BioMed Central, 2006)
Specific complex interactions between soil bacteria belonging to Rhizobium, Sinorhizobium, Mesorhizobium, Phylorhizobium, Bradyrhizobium and Azorhizobium commonly known as rhizobia, and their host leguminous plants result in development of root nodules. Nodules are new organs that consist mainly of plant cells infected with bacteroids that provide the host plant with fixed nitrogen. Proper nodule development requires the synthesis and perception of signal molecules such as lipochitooligosaccharides, called Nod factors that are important for induction of nodule development. Bacterial surface polysaccharides are also crucial for establishment of successful symbiosis with legumes. Sugar polymers of rhizobia are composed of a number of different polysaccharides, such as lipopolysaccharides (LPS), capsular polysaccharides (CPS or K-antigens), neutral β-1, 2-glucans and acidic extracellular polysaccharides (EPS). Despite extensive research, the molecular function of the surface polysaccharides in symbiosis remains unclear. This review focuses on exopolysaccharides that are especially important for the invasion that leads to formation of indetermined (with persistent meristem) type of nodules on legumes such as clover, vetch, peas or alfalfa. The significance of EPS synthesis in symbiotic interactions of Rhizobium leguminosarum with clover is especially noticed. Accumulating data suggest that exopolysaccharides may be involved in invasion and nodule development, bacterial release from infection threads, bacteroid development, suppression of plant defense response and protection against plant antimicrobial compounds. Rhizobial exopolysaccharides are species-specific heteropolysaccharide polymers composed of common sugars that are substituted with non-carbohydrate residues. Synthesis of repeating units of exopolysaccharide, their modification, polymerization and export to the cell surface is controlled by clusters of genes, named exo/exs, exp or pss that are localized on rhizobial megaplasmids or chromosome. The function of these genes was identified by isolation and characterization of several mutants disabled in exopolysaccharide synthesis. The effect of exopolysaccharide deficiency on nodule development has been extensively studied. Production of exopolysaccharides is influenced by a complex network of environmental factors such as phosphate, nitrogen or sulphur. There is a strong suggestion that production of a variety of symbiotically active polysaccharides may allow rhizobial strains to adapt to changing environmental conditions and interact efficiently with legumes.